İkinci Dünya Savaşı'nda Sovyet propagandası (1939-1945) - İnce, Mehmet Fatih (My University, 2023)
Bu çalışmada, Rusya tarihinin önemli dönüm noktalarından olan İkinci Dünya Savaşı sırasında Sovyet yönetimi tarafından uygulanan propaganda faaliyetleri ele alınmıştır. İkinci Dünya Savaşı resmî olarak 3 Eylül 1939 tarihinde başlamış olsa da Sovyetler Birliği için savaş, Almanya’nın Barbarossa Harekâtı kapsamında Sovyet topraklarını işgal etmesiyle 22 Haziran 1941 tarihinde başlamıştır. Sovyetler Birliği için bir varoluş mücadelesi anlamını taşıyan bu savaş yalnızca cephede değil cephe gerisinde de yürütülmüştür. Psikolojik savaş kapsamında yürütülen Sovyet propagandasının bazı konu başlıkları savaştan önce devreye sokulmuştur. Sovyet idaresinin kurulduğu tarihten itibaren yürütülen üretim propagandası, Stalin’in kült liderlik propagandası, partizan propagandası, nefret propagandası ve milliyetçilik propagandası, Büyük Vatanseverlik Savaşı boyunca Sovyet yönetimi tarafından daha yoğun uygulanan propaganda başlıklarıdır. Sovyet yönetimi savaşın yalnızca Ruslar ya da belirli bir grubun inisiyatifiyle kazanılamayacağına kanaat getirmiş, sözlü ve basılı yayın organlarında savaşa Sovyetler Birliği sınırları içinde yaşayan tüm halkların dâhil olduğu, Sovyet halkının mücadelede söz sahibi olduğu mesajını vermiştir. Bu çalışmanın amacı yalnızca Rus tarihinin değil, Sovyetler Birliği sınırları içinde yaşayan milletlerin kaderini değiştiren olayların yaşandığı, İkinci Dünya Savaşı sırasında yürütülen propaganda faaliyetlerinin önemini açıklamak ve sonraki ilmî çalışmalara ışık tutmaktır.

In this study, the propaganda activities implemented by the Soviet administration during the Second World War, which is one of the important turning points in the history of Russia, are discussed. Although the Second World War officially began on 3 September 1939, the war began on 22 June 1941 for Soviet Union due to Germany invaded Soviet territory as part of Operation Barbarossa. This war which meant an existence struggle for the Soviet Union, was carried out not only at the front but also behind the front. Some of the topics of Soviet propaganda carried out within the scope of psychological warfare were put into effect before the war. Production propaganda that carried out since the establishment of the Soviet administration, Stalin’s cult leadership propaganda, partisan propaganda, hatred propaganda and nationalism propaganda are propaganda titles that were applied more intensively by the Soviet administration during the Great Patriotic War. The Soviet administration came to the conclusion that the war could not be won only with Russian or with the initiative of a certain group and gave the message in newspapers and magazines that all peoples living within the borders of the Soviet Union were involved in the war and that the Soviet people had in the struggle. The aim of this study is to explain the importance of propaganda activities carried out not only in Russian history, but also in the Second World War, events that changed the fate of the nations living within the borders of the Soviet Union took place in those years, and to shed light on subsequent studies.
Keywords: Büyük Vatanseverlik Savaşı; Dünya Savaşı, 2, 1939-1945; Great Patriotic War; İkinci Dünya Savaşı; Propaganda; Propaganda Soviet Union; Second World War; Soviet Propaganda; Soviet Union; Sovyet Propagandası; Sovyetler Birliği; World War, 1939-1945